(untitled) (Hematology Meeting Reports, 2009)
Nearly half of patients with relapsed chronic lymphocytic leukemia (CLL) develop loss of 17p13, resulting in loss of the p53 tumor suppressor gene and resistance to most standard therapies. Thus, new therapies for relapsed CLL patients with del(17p13) and other high-risk cytogenetic abnormalities are needed. The synthetic flavone flavopiridol down-regulates the anti-apoptotic protein Mcl-1 and induces apoptosis of CLL cells in vitro. However, initial clinical trials using 24-72-hour continuous intravenous infusion (CIVI) dosing schedules observed no clinical activity, due to extensive drug binding to human plasma proteins and inadequate free flavopiridol concentrations. Pharmacokinetic modeling indicated that a 30-minute IV bolus followed by a 4-hour CIVI would achieve serum concentrations which induced in vitro apoptosis. A phase I study of this novel dosing regimen in 58 patients demonstrated that flavopiridol is highly active in patients with relapsed, genetically high-risk CLL. The dose limiting toxicity was acute tumor lysis syndrome (TLS) resulting in fatal hyperkalemia in one patient. Increased monitoring of serum potassium levels, aggressive intervention for hyperkalemia, and limitation of treatment to patients with white blood cell counts less than 200×109/L allowed flavopiridol to be administered safely. The response rate was 47%, with a median progression free survival of 11 months in responders, and flavopiridol was active in patients with high-risk features such as del(11q22) and del(17p13) or bulky nodal disease. Mean area under the curve (AUC) of drug exposure correlated with response to therapy, and mean AUC of the glucoronide metabolite correlated with severe TLS. A recently completed phase II study in 63 patients confirmed these results. Thus, flavopiridol is highly active in relapsed, high-risk CLL. An international, multi-center registration study is ongoing.